Faktor risiko persalinan vakum ekstraksi pada ibu dengan kala II lama terhadap kejadian ikterus neonatorum di RSUD Wates tahun 2009-2010 - Dameria M.P; Sabar Santoso; Sumarah Sumarah (Poltekkes Kemenkes Yogyakarta, 2012)
ln 2007 infant Mortality Rate (IMR) in Indonesia is 269/1000 live births. one cause of infant mortality in Indonesia is a birth trauma. Sefalhematoma birth trauma duo to Vacuum Extraction (VE) is one of the causes of neonatal jaundice. incidence of cases with VE deliveries in hospitals Wates in 2O1O as much as 6.4% and the incidence of jaundice due to childbirth vacuum as much as 11.7%. This study was Knowing the risks of a vacuum extraction delivery with a prolonged second stage on the incidence of neonatal jaundice of Wates hospitals in 2010. The type of case-control study with the independent variable is the delivery type and the dependent variable is incident neonatal jaundice. The whole population of all babies born in hospitals Wates from March 2OO8 to December 2070. Cases sample is infants with jaundice by 129 babies in hospitals Wates. The control sample is infant without jaundice by 129 babies in hospitals Wates. the Results of the highest maternal characteristics based on P1 parity (primipara). there is a relationship between parity P1 with the incidence of jaundice and oR of 2.095. There is no relationship between parity P>1 (Sekundipara and multipara) with the incidence of jaundice- The highest incidence of infant jaundice is the type of vacuum deliveries than types of spontaneous labor. The results of the chi-square I of 8.935 at p-value < 0.003 in which p-value < 0.005 can be concluded there is a relationship between labor vacuum with the prolonged second stage the on the incidence of neonatal jaundice. The results of the contingency coefficient of 0.183 means that a labor vacuum with the incidence of jaundice has a very low. Obtained OR value of 2.124 means that the labor vacuum with a prolonged second stage as a risk factor for neonatal jaundice at 2 times.